Upaya Penanganan Kesulitan Membaca Permulaan pada Anak di Rumah Belajar Dusun IV Lamtoro II RT. V - Azzahra, Azzahra; Fajar Utama Ritongga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
This field work practice is motivated by problems which show that children's reading skills are not yet optimal in their ability to recognize simple words, children are not yet able to arrange letters into words, arrange syllables into words. The street vendors are held at the Children's Learning House which is located in Dusun IV Lamtoro II, RT. V Bandar Klippa Village, Kec. Percut Sei Tuan, Deli Serdang Regency, North Sumatra. The aim of this street vendor is that students are expected to be able to apply the groupwork method to a mini project which will be one of the assessments in this street vendor activity. By using social work intervention methods with groups (groupwork). Mezzo (groupwork) interventions help individuals, groups, families, organizations and communities in order to strengthen and improve their capacities in order to overcome problems or restore client social functioning. With this mini project, it is hoped that it will improve children's reading skills in the Learning House, which totals 5 people. The data obtained in this study is through the results of the assessment that is carried out is a generalist assessment that includes the realm of mezzo practice in one client case. The mezzo assessment is carried out on the conditions of the client's closest social environment such as the client's family or peers accompanied by observations or observations of children's activities while learning to read through programs that have been designed. Data on children's learning outcomes has increased significantly. Children's reading ability has increased. Thus it can be concluded that a series of programs to build children's study habits can improve children's reading skills at the Children's Learning House in Dusun IV Lamtoro II RT. V